Some Red and Lateritic Soils of Low Rainfall Regions and their Afforestation Problems - Yadav, J. S. P. (Indian Forester, 1968)
Analytical data about important physical and chemical properties of a few lateritic and red soil profiles from the low rainfall areas or Andhra Pradesh, Madras, Mysore and M.P. have been presented. The data reveal that the soils vary in texture and are generally acidic and non-calcareous excepting the lowest depths of two red soil profiles which are calcareous and only slightly alkaline. Most soils contain low amount of Nitrogen, Calcium, Magnesium, Potassium and Phosphorus with the exception of one red soil developed on basalt in M.P. which possesses strikingly high values of Calcium, Magnesium, cation exchange capacity and water holding power. The need for conserving soil and moisture and for improving the ferti1ity status together with the choice of suitable soil working methods and species has been indicated, so that these areas may be afforested.